Transitions from hospital to home: A mixed methods study to evaluate pediatric discharges in Uganda - Kabajaasi, Olive; Trawin, Jessica; Derksen, Brooklyn; Komugisha, Clare; Mwaka, Savio; Waiswa, Peter; Nsungwa-Sabiiti, Jesca; Ansermino, J. Mark; Kissoon, Niranjan; Duby, Jessica; Kenya-Mugisha, Nathan; Wiens, Matthew O. (PLOS Global Public Health, 2023)
The World Health Organization (WHO) Integrated Management of Childhood Illness (IMCI) guidelines recognize the importance of discharge planning to ensure continuation of care at home and appropriate follow-up. However, insufficient attention has been paid to post discharge planning in many hospitals contributing to poor implementation. To understand the reasons for suboptimal discharge, we evaluated the pediatric discharge process from hospital admission through the transition to care within the community in Ugandan hospitals. This mixed methods prospective study enrolled 92 study participants in three phases: patient journey mapping for 32 admitted children under-5 years of age with suspected or proven infection, discharge process mapping with 24 pediatric healthcare workers, and focus group discussions with 36 primary caregivers and fathers of discharged children. Data were descriptively and thematically analyzed. We found that the typical discharge process is often not centered around the needs of the child and family. Discharge planning often does not begin until immediately prior to discharge and generally does not include caregiver input. Discharge education and counselling are generally limited, rarely involves the father, and does not focus significantly on post-discharge care or follow-up. Delays in the discharge process itself occur at multiple points, including while awaiting a physical discharge order and then following a discharge order, mainly with billing or transportation issues. Poor peri-discharge care is a significant barrier to optimizing health outcomes among children in Uganda. Process improvements including initiation of early discharge planning, improved communication between healthcare workers and caregivers, as well as an increased focus on postdischarge care, are key to ensuring safe transitions from facility-based care to home-based care among children recovering from severe illness.
Keywords: World Health Organization (WHO); Integrated Management of Childhood Illness; Post discharge planning